PLAN DE MARKETING PARA LA COOPERATIVA DE AHORRO Y CRÉDITO “CREDIAMIGO LTDA.” – AGENCIA GONZANAMÁ PARA EL PERIODO 2019 - JIMÈNEZ ZAPATA, ADRIANA DEL CISNE (2019)
The thesis aims to develop a Marketing Plan for the Savings and Credit Cooperative “Crediamigo Ltda.” - Gonzanamá Agency, of the Gonzanamá Canton, Loja Province. For the realization the deductive method was used to perform the analysis of the PESTE factors and of the 5 forces of Porter in order to perform the external and competitive analysis; In the internal analysis a description of the history of the company was made and the analysis of each of the marketing variables (product, price, place, promotion), by applying the techniques of the interview to the head of agency and employees of the Cooperative, and the surveys of its members; and the inductive method that allowed to elaborate the proposal of the Marketing Plan and the due conclusions and recommendations. This research has as a general objective “To carry out a Marketing Plan for the Cooperative de savings and credit Crediamigo Ltda. - Gonzanamá Agency. For the period 2019”. The specific objectives are: diagnose internal and external factors that affect the development of the organization, allowing to know the situation of the agency and its environment, determine a SWOT analysis (strengths, weaknesses, threats and opportunities), perform a market investigation that allows you to identify potential clients and their needs and define the marketing mix of the Cooperative de savings and credit Crediamigo Ltda. - Gonzanamá Agency. Based on the results of the different analyzes of the context and business environment, the main opportunities, threats, strengths and weaknesses of the Cooperative were defined, in order to prepare the EFE matrix that resulted in 2.74 which means that the Cooperative is located on a good level because it is responding to the opportunities and threats of the environment; and the EFI matrix that gave a score of 2.76 is interpreted that the Cooperative is in a strong internal 5 position because there are more strengths than weaknesses; then the strategies in the High Impact Matrix were determined that helped develop the necessary strategies for the cooperative. In the discussion, the strategic objectives were raised and the business philosophy was proposed, then matrices of the proposed objectives were made detailing each of them with their activities, strategies and responsible, then the general budget of all the strategic objectives that will be of $ 5860.00, as well as their respective schedule for this year. In the end, the conclusions of the most important points of the investigation and recommendations that allow working efficiently.